Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s11103-022-01287-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the glutamine synthetase (GS) gene family in four wheat species and functional analysis of Ta4D.GSe in Arabidopsis thaliana

Abstract: Drought stress can negatively impact crop yield and quality. Improving wheat yields under drought stress is a major objective of agronomic research. Glutamine synthetase (GS) is a key enzyme of nitrogen metabolism that is critical to plant growth and development in abiotic stress response. However, to date, no systemic characterization of the GS genes has yet been conducted in wheat and its close relatives. We identified a total of 15 GS genes in Triticum aestivum (2n = 6x = 42; AABBDD), as well as 9 GS genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Correlation analysis revealed that a total of 25 genes were positively correlated with glutenin, with correlation coefficients ranging from 0.53 to 0.95, and that 20 genes were negatively correlated with glutenin content, with correlation coefficients ranging from 0.50 to 0.95. GS is closely related to the high grain protein content and nitrogen efficiency of wheat, and its activity significantly affects protein and amino acid contents ( Yin et al., 2022 ). The nitrogen absorbed by wheat is catalysed by GS to produce glutamine (Gln) by the ATP-dependent condensation reaction of ammonium with glutamic acid (Glu), which then provides the N group directly through Glu for the biosynthesis of proteins, amino acids, and other nitrogen-containing compounds ( Nigro et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analysis revealed that a total of 25 genes were positively correlated with glutenin, with correlation coefficients ranging from 0.53 to 0.95, and that 20 genes were negatively correlated with glutenin content, with correlation coefficients ranging from 0.50 to 0.95. GS is closely related to the high grain protein content and nitrogen efficiency of wheat, and its activity significantly affects protein and amino acid contents ( Yin et al., 2022 ). The nitrogen absorbed by wheat is catalysed by GS to produce glutamine (Gln) by the ATP-dependent condensation reaction of ammonium with glutamic acid (Glu), which then provides the N group directly through Glu for the biosynthesis of proteins, amino acids, and other nitrogen-containing compounds ( Nigro et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the role of GS activity in response to fertilization has been widely investigated, and its relationship with stresses such as drought and high temperature has also been explored [13]. In most plants, GS exists in two forms, including cytoplasmic GS1 and chloroplasts GS2 [14]. In addition, members of the GS gene family have been identified in many plants, such as Arabidopsis (Arabidopsis thaliana (L.) Heynh.)…”
Section: Introductionmentioning
confidence: 99%